The Use of Emergency Lights and Sirens by Ambulances and Their Effect on Patient Outcomes and Public Safety: A Comprehensive Review of the Literature. Issue 2 (30th January 2017) - Murray, Brett; Kue, Ricky
Abstract: The benefits of emergency lights and sirens (L&S) use as warning devices by ambulances continue to be a debated topic in Emergency Medical Services (EMS). While the most widely studied aspect of L&S use has been related to their effect on ambulance response and transport times, the literature suggests minimal time savings with more questionable impact on actual patient outcomes. As L&S use has been shown to increase the risk for vehicle crashes, the secondary concern of ambulance design and safety also becomes an important aspect on potential design recommendations that could mitigate the effects of a crash on patients, EMS providers, and the general public. The least studied aspect of L&S use (and probably the most important) is their effect on patient outcomes and quality of medical care during transport. The current evidence suggests no significant improvement on patient outcomes and potential worsening to certain aspects of patient care during transport. The purpose of this review was to examine the current literature regarding ambulance L&S use and the risks they pose to EMS providers, patients, and the general public. In doing so, it will provide sound background for EMS leaders to better develop policies governing the use of L&S by ambulances and promote better research in the patient outcomes effect associated with their use. This review offers some strategies in mitigating the risks associated with L&S use, such as ways to reduce their overall use and modifying other related factors to emergency medical vehicle collisions (EMVCs). B Murray, R Kue .The use of emergency lights and sirens by ambulances and their effect on patient outcomes and public safety: a comprehensive review of the literature .Prehosp Disaster Med .2017 ;32 (2 ):209 –216 .